Peran Kepemimpinan Transformasional Dalam Meningkatkan Inovasi Organisasi Melalui Dukungan Terhadap Inovasi Yang Dilakukan - Ekobelawati, Fransiska; Zulimi, Zulimi (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) IBE Indonesia, 2024)
This research investigates the significant relationship between the role of transformational leadership in increasing organizational innovation through support for innovation carried out by fifty-three coffee cafes in the cities of Pontianak and Kuburaya. This research uses to measure what the concept should measure. For Partial Least Squares (PLS), the SmartPLS 4.0 program can be used to measure construct validity by testing convergent and discriminant validity. The convergent validity test with the SmartPLS 4.0 program shows the loading coefficient value for each construct indicator. A high factor loading value indicates that each construct indicator is concentrated at one point. A rule of thumb generally used to assess convergent validity is that factor loading values ​​greater than 0.7 in confirmatory studies and factor loading values ​​between 0.6 and 0.7 in exploratory studies are still acceptable and average variance (AVE) values ) should. greater than 0.5. In addition, the validity and reliability of the measurement instruments were tested. This study confirmed the validity of the survey questions for the three constructs The Role of Transformational Leadership in Increasing Organizational Innovation Through Support for Implemented Innovation and produced satisfactory reliability for the measurement. In conclusion, this research highlights the significant impact of the role of transformational leadership in increasing organizational innovation and through supporting innovation carried out by organizations. These findings provide valuable insights for organizations that want to increase organizational innovation and organizations must also support the innovation that has been implemented by leaders